Preparation method of industrial-grade large-size hexagonal boron nitride single crystal

By placing the metal core column in the boron nitride tube under high temperature and high pressure and growing under pressure, the problem of difficult to prepare high-quality, large-size h-BN single crystals in the prior art is solved, and efficient and low-cost single crystal growth is achieved, and yield and crystal quality are improved.

CN119838506AActive Publication Date: 2025-04-18HARBIN INSTITUTE OF TECHNOLOGY (SHENZHEN) (INSTITUTE OF SCIENCE AND TECHNOLOGY INNOVATION HARBIN INSTITUTE OF TECHNOLOGY SHENZHEN) +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510087964.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-18
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

It is difficult to prepare high-quality, large-sized single crystals of hexagonal boron nitride (h-BN) in the prior art, and the commonly used high-pressure and high-temperature methods have limited sizes, low yields, and high costs.

Method used

The metal core column is placed in a boron nitride tube by using the high temperature and high pressure method, pressurized to a growth pressure of 2 to 6 GPa, heated to a growth temperature of 1800 to 3000°C, and maintained at this temperature for 0.5 to 2 hours, and the crystal growth is controlled, and the metal is finally removed to obtain a single hexagonal boron nitride crystal.

Benefits of technology

It realizes rapid dissolving of B and N atoms under high temperature and high pressure, controls crystal growth, improves the yield and quality of single crystals, and ensures the high cleanliness and excellent performance of single crystals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838506A_ABST
    Figure CN119838506A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an industrial-grade large-size hexagonal boron nitride single crystal, which adopts Fe, Ni, Cr, Fe / Ni, Fe / Cr and Ni / Cr alloy as metal melts, and uses a high-purity boron nitride tube for wrapping, so that the rapid growth of centimeter-grade or even close-to-inch-grade high-quality h-BN block single crystal can be realized under an ultra-high temperature condition. According to the contact mode provided by the invention, B and N atoms can be quickly dissolved into the melt at high temperature and high pressure, the heat preservation time is shortened, meanwhile, the nucleation position and nucleation amount of hexagonal boron nitride are effectively controlled, crystals are controlled to grow from the contact position to the center of the melt, the whole melt is filled with the crystals, the yield of single crystals can be greatly increased, and the production cost is reduced. Meanwhile, the melt is only in contact with the parent raw material, so that external impurities can be prevented from entering, and the high cleanliness of the single crystal is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of single crystal material preparation, and specifically relates to a method for preparing an industrial-grade large-size hexagonal boron nitride single crystal. Background Art

[0002] Hexagonal boron nitride (h-BN) has a two-dimensional layered structure similar to graphite and is known as "white graphite". It has strong BN sp² hybrid covalent bonds within the layer, and the interlayers are connected by weak van der Waals forces, which enables it to be cleaved at the atomic level to prepare single-layer, double-layer and other two-dimensional (2D) materials, so it is also called "white graphene". This material exhibits many important properties and is indispensable in scientific research and industrial production. More importantly, unlike graphite and other 2D materials, "white graphene" shows unique electrical insulation properties, with a band gap of 5.9 eV and low dielectric loss, which is unique among 2D materials. In addition, it has a high lattice matching with other 2D materials, making it indispensable as a substrate insulating material in quantum devices such as graphene and flexible electronic devices. With the development and application of two-dimensional quantum materials such as graphene, as well as the development of the flexible electronic device industry, this will bring important opportunities for the application of h-BN. However, these high-end applications usually require high-quality, large-size single crystal h-BN to prepare large-area single-sheet "white graphene". Due to the high melting point of h-BN, it is challenging to grow single crystals under normal pressure conditions. The samples currently available on the market are usually low-quality micron-level powders, which cannot meet the strict requirements of future high-end technology industries on material performance. Therefore, it is necessary to explore new preparation methods and approaches.

[0003] The properties of h-BN single crystal layers change with the change of crystal orientation. In polycrystalline h-BN, the different crystal orientations of each grain significantly affect its macroscopic properties. In addition, the grain boundaries in the polycrystals also interfere with its physical properties. Therefore, in practical applications, the performance of single crystal samples is significantly better than that of polycrystalline samples. Ideally, h-BN with low defect density and high purity can show the best performance, because the defect density will have an adverse effect on the heterogeneous layer, while high-purity single crystals can ensure maximum optical transparency. Therefore, the preparation of high-quality, large-size h-BN single crystals is crucial for the research of future electronic devices.

[0004] The preparation of h-BN single crystals began in the 1970s. Ishii et al. used silicon as a flux for the first time and obtained h-BN single crystals with a diameter of about 2 mm and a thickness of about 10 um in a nitrogen environment. However, due to the influence of impurities, these h-BN crystals are yellow and contain a large number of nitrogen vacancy defects. Subsequently, Kubota et al. used nickel, nickel-molybdenum and nickel-chromium instead of silicon as fluxes to study the growth of h-BN single crystals in different fluxes. The results show that under atmospheric pressure, due to the low solubility of nitrogen in Ni flux, the growth rate is too low; when using nickel-molybdenum solvent, the grown crystals are polycrystalline with a diameter of several hundred um; and when using nickel-chromium solvent, it is beneficial to increase the thickness of the crystal. In order to increase the size of h-BN single crystals, Edgar et al. dissolved polycrystalline powder in a nickel-chromium alloy flux and heated it to 1500 °C under a nitrogen flow at normal pressure, and then slowly cooled it to 1250 °C at a rate of 4 °C / h, and finally obtained h-BN single crystals with a crystal diameter of 1-2 mm and a single particle diameter of 100-200 µm. In order to prepare flaky h-BN under simpler conditions, Liang Dan et al. used boric acid and melamine as reactants and NaCl-KCl as a molten salt system to prepare single crystal h-BN in air without nitrogen or ammonia protection by microwave heating of molten salt. Studies have shown that after 60 minutes of microwave heating, hexagonal flaky h-BN with complete crystal form can be formed, making it possible to prepare flaky h-BN under simpler and milder conditions. However, the size of h-BN prepared by this method is small, only reaching the um level. In addition to the above-mentioned flux systems, the Ba-BN system is also an effective flux for growing single crystal h-BN, but its strong hygroscopicity and easy oxidation are challenges. Since trace oxygen contamination may seriously interfere with the crystal growth process, the experiment needs to be carried out in a dry nitrogen environment. Therefore, finding alternative solvents to obtain high-quality h-BN single crystals remains a major challenge in this method. The high defect concentration of samples prepared under normal pressure conditions is also an important factor limiting the use of this material in cutting-edge applications.

[0005] So far, large-sized h-BN single crystals are still difficult to prepare. Researchers have tried to meet the use requirements through thin film preparation, including chemical vapor deposition, magnetron sputtering, molecular beam epitaxy and ion beam assisted electron beam deposition. Dahal et al. used triethylboron and ammonia as precursors of boron and nitrogen, and successfully prepared h-BN thin films by metal organic chemical vapor deposition. Xiang et al. prepared thin films by magnetron sputtering deposition of bulk polycrystalline boron hexanitride targets, and Sutter et al. sputtered boron onto Ru (0001) epitaxial films in a nitrogen / argon environment, and also obtained a small amount of single crystal films. In the study of molecular beam epitaxial growth of h-BN thin films, Gupta et al. used NH3 as a nitrogen source to deposit h-BN thin films on sapphire (0001). Infrared spectroscopy confirmed that it was h-BN, but electron diffraction showed that it was a polycrystalline structure. There are many problems in the preparation of h-BN thin films, such as the development and use of high-performance precursors. As people's requirements for h-BN coating quality, process controllability and safety increase, traditional halogen-containing two-component precursors have gradually failed to meet the needs. Due to the complexity of chemical vapor deposition, the deposition mechanism of h-BN is not yet fully understood, and it is highly dependent on the size and structure of the production equipment. The production process is complex and the cost is high.

[0006] To date, the most successful method for preparing h-BN single crystals is the high-pressure and high-temperature method. Watanabe et al. used boron nitride powder as the raw material, mixed the flux Ba-BN compound with boron nitride, heated it to 1500-1750℃ at a pressure of 5.5 GPa, and kept it warm for 20 hours. In order to reduce the introduction of impurities, the powder was heat treated at 2100℃ for 2 hours before the experiment, and the physically adsorbed oxygen on the surface of the raw material was removed by nitrogen flow. After the experiment, the sample was dissolved in hot aqua regia to obtain the grown crystals, and the crystal size was about several hundred um. Similarly, Taniguchi et al. used Ba3B2N4 as a flux, controlled the growth temperature between 1500-1650℃ at a pressure of 4-5 GPa, and kept it warm for 20 to 80 hours. Although the size of the single crystal increased with the increase of the holding time, it was still in the micron range. In recent years, Zhigadlo has grown transparent and colorless h-BN single crystals from Mg-BN using high pressure and high temperature technology. The experiment uses magnesium flakes, amorphous boron powder and boron nitride powder as raw materials, and controls the molar ratio of Mg: B: BN to be 1:12: 0.1. After removing volatile substances such as oxygen impurities, the crucible filled with the Mg-B-BN mixture is placed in a graphite heater and a pyrophyllite cube. During the preparation process, the sample is gradually compressed to the required pressure and heated to 1800-2100℃ within 1 hour, kept warm for 0.5-2 hours, and then cooled to 20℃ within 1 hour. The BN crucible is then broken and heated in a vacuum at 750℃ for 0.5 hours to remove excess Mg. This method can grow plate-like h-BN crystals with a maximum width of 2.5 mm and a thickness of 10 µm, but the process is complicated and post-processing may introduce impurities, affecting the final crystal quality. At present, among the methods for preparing single crystal h-BN, the h-BN single crystal prepared by the molten salt precipitation method is small in size and requires several hours of heat preservation; the deposition method such as CVD is complicated and costly due to equipment limitations; the h-BN single crystal prepared by high temperature and high pressure technology can reach the mm level in size, but requires dozens of hours of heat preservation, a long cycle, and high cost. Therefore, the rapid, low-cost, and large-size h-BN single crystal preparation is still an engineering and scientific problem that needs to be solved urgently.

[0007] Although Japanese scientists have successfully prepared high-quality single-crystal h-BN through high-temperature and high-pressure methods, due to the size limitations of the high-pressure cavity and the limitations of high-temperature and high-pressure technology, the single crystals prepared are only 1-3 mm, and the yield is extremely low, which can only meet scientific research purposes at this stage. Similarly, Edgar et al. used Fe under normal pressure to claim that they had grown centimeter-level single crystals under normal pressure, and they had to be peeled off with tape to obtain a single complete crystal. The size of the single crystal is questionable, and the yield is extremely low. Therefore, it is of great significance to develop a new high-temperature and high-pressure preparation method to prepare high-quality single-crystal h-BN with industrial-grade sizes of centimeters or inches. Summary of the invention

[0008] The object of the present invention is to overcome at least one disadvantage of the prior art and to provide a method for preparing industrial-grade large-size hexagonal boron nitride single crystals.

[0009] The technical solution adopted by the present invention is: The present invention provides a method for preparing an industrial-grade large-size hexagonal boron nitride single crystal, comprising the following steps: 1) Place the metal core column in the boron nitride tube and pressurize it to a growth pressure of 2 to 6 GPa. After reaching the set pressure, enter the pressure holding stage; 2) Heating to 1000-1500°C at a rate of 10-20°C / min and keeping warm to release internal stress; 3) Continue heating at a rate of 10-20 °C / min to reach a growth temperature of 1800-3000 °C, and maintain at this temperature for 0.5-2 hours; 4) Control the crystal growth by cooling at a rate of 1 to 5 °C / min. After the crystal growth is completed, remove the metal, wash and dry to obtain the hexagonal boron nitride single crystal.

[0010] In some examples, the ratio of the diameters of the metal core column and the boron nitride tube is 0.65 to 0.7.

[0011] In some examples, the ratio of the height of the metal core column to the height of the boron nitride tube is 0.65-0.67.

[0012] In some examples, the diameter difference between the boron nitride tube and the metal core column is not less than 2 mm.

[0013] In some examples, the metal core column is made of Fe, Ni, Cr or Fe / Ni, Fe / Cr, Ni / Cr alloy.

[0014] In some examples, the growth pressure is 2-5.5 GPa.

[0015] In some examples, the growth temperature is 2000-2200°C.

[0016] In some examples, the single crystal is grown at a pressure of 4 GPa and maintained at 2200° C. for 1 h.

[0017] In some examples, the purity of the boron nitride tube is not less than 99.999%.

[0018] In some examples, the metal is removed by pickling.

[0019] The above features can be combined arbitrarily as long as they do not conflict with each other.

[0020] The beneficial effects of the present invention are: 1) The contact method provided by the present invention can quickly dissolve B and N atoms into the melt under high temperature and high pressure, thereby reducing the insulation time; 2) The contact method provided by the present invention can effectively control the nucleation position and nucleation amount of hexagonal boron nitride, and can control the growth of the crystal from the contact position to the center of the melt; 3) The contact method provided by the present invention can realize the growth of crystals to fill the entire melt, which can greatly increase the yield of single crystals.

[0021] 4) The contact method provided by the present invention can achieve that the melt is in contact only with the matrix raw material, thereby preventing the entry of external impurities and ensuring the high cleanliness of the single crystal. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Schematic diagram of the high-pressure chamber assembly required for the growth of h-BN single crystals, including: (a) schematic diagram of the pressurization of the high-pressure assembly; (b) actual picture of the pyrophyllite assembly; (c) h-BN tube wrapped with a metal core column (Fe or Ni, Cr, Fe / Ni, Fe / Cr, Ni / Cr column); (d) schematic diagram of the assembly of the h-BN tube and the internal metal core column (Fe or Ni, Cr, Fe / Ni, Fe / Cr, Ni / Cr column).

[0023] Figure 2 (a) Process curve and (b) growth principle diagram of h-BN single crystal growth.

[0024] Figure 3 Hexagonal boron nitride is grown using iron (Fe), nickel (Ni) and chromium (Cr) as melts.

[0025] Figure 4 Characterization of the size and yield of h-BN single crystals, including: (a) h-BN single crystals grown at 5 GPa pressure and different temperatures; (b) h-BN single crystals grown at 2200 °C under different pressures; (c) h-BN single crystals obtained by keeping at 5 GPa pressure and 2200 °C for different time periods; (d) h-BN single crystal yield obtained by keeping at 4 GPa pressure and 2200 °C for 1 h; (e) h-BN single crystal size obtained by keeping at 4 GPa pressure and 2200 °C for 2 h.

[0026] Figure 5 Hexagonal boron nitride single crystals were grown at 5 GPa, (a) 1800 °C and (b) 1950 °C.

[0027] Figure 6 Characterization of the quality of h-BN single crystal. (a) XRD spectrum; (b) low wave number Raman spectrum; (c) Raman spectrum of h-BN single crystal sample E 2gVibration mode; (d) Relationship between the half-width and peak position of the E2g vibration mode in the Raman spectrum of the h-BN single crystal sample (e) UV-visible spectrum of the h-BN single crystal and (f) dielectric characterization of the thin layer h-BN single crystal sample. DETAILED DESCRIPTION

[0028] The present invention provides a method for preparing an industrial-grade large-size hexagonal boron nitride single crystal, comprising the following steps: 1) Place the metal core column in the boron nitride tube and pressurize it to a growth pressure of 2 to 6 GPa. After reaching the set pressure, enter the pressure holding stage; 2) Heating to 1000-1500°C at a rate of 10-20°C / min and keeping warm to release internal stress; 3) Continue heating at a rate of 10-20 °C / min to reach a growth temperature of 1800-3000 °C, and maintain at this temperature for 0.5-2 hours; 4) Control the crystal growth by cooling at a rate of 1 to 5 °C / min. After the crystal growth is completed, remove the metal, wash and dry to obtain the hexagonal boron nitride single crystal.

[0029] Large size means that the length of the hexagonal boron nitride single crystal is not less than 1 mm.

[0030] In some examples, the diameter ratio of the metal core column to the boron nitride tube is 0.65 to 0.7, which can ensure that there is sufficient contact area between the metal core column and the boron nitride tube, facilitating the growth of hexagonal boron nitride single crystals.

[0031] In some examples, the height ratio of the metal core column to the boron nitride tube is 0.65 to 0.67, so that the boron nitride can fully contact the metal core column, facilitating the growth of the hexagonal boron nitride single crystal.

[0032] In some examples, the diameter difference between the boron nitride tube and the metal core column is not less than 2 mm.

[0033] In some examples, the metal core column is made of Fe, Ni, Cr or Fe / Ni, Fe / Cr, Ni / Cr alloy. Experimental data show that the metal core column made of these metals or alloys can be used as a solute under high temperature and high pressure to better dissolve boron nitride, which is conducive to obtaining high-quality, large-sized hexagonal boron nitride single crystals.

[0034] In some examples, the growth pressure is 2-5.5 GPa.

[0035] In some examples, the growth temperature is 2000-2200° C. At this temperature, hexagonal boron nitride single crystals with better quality and larger size can be obtained.

[0036] In some examples, the single crystal is grown at a pressure of 4 GPa and maintained at 2200° C. for 1 hour. Data show that the hexagonal boron nitride single crystal under this condition has better performance.

[0037] In some examples, the purity of the boron nitride tube is not less than 99.999%. High-purity boron nitride tubes are more conducive to obtaining high-quality hexagonal boron nitride single crystals.

[0038] The metal can be removed by any method that does not damage or less damages the hexagonal boron nitride single crystal. In some examples, the metal is removed by pickling. Pickling is simple to operate and has good results. The metal can also be removed by electrolysis or other methods.

[0039] The above features can be combined arbitrarily as long as they do not conflict with each other.

[0040] The following disclosure provides many different embodiments or examples for implementing different solutions of the present invention. Example

[0041] The invention adopts a high temperature and high pressure method to grow h-BN bulk single crystal. The experiment is carried out on a six-sided top press device (DS650). Figure 1 Schematic diagram showing the assembly of the high-pressure chamber for h-BN single crystal growth. Figure 1 (a) shows the assembled pyrophyllite components (see Figure 2 ) is placed between six tungsten carbide (WC) pressure hammers of a six-sided top press. Pressure is applied through the piston cylinder, and the WC hammer slowly squeezes the pyrophyllite block, thereby generating high pressure inside it. The high-purity boron nitride tube wraps the high-purity metallic iron (Fe) column and is assembled with other high-pressure chamber components in an argon-filled glove box to prevent the introduction of an oxidizing atmosphere. The h-BN tube has an outer diameter and height of 22 mm, an inner diameter of 15.1 mm, and the high-purity Fe column has a diameter of 15 mm and a height of 10 mm. An Fe column that is too high or too large in diameter may overflow the h-BN tube at high temperatures, resulting in instability of the high-pressure chamber and failure of the experiment.

[0042] Figure 2(a) shows the process curve during the growth of h-BN single crystal. In the experiment, the phyllite assembly block of the six-sided top press was first pressurized to a target pressure of 2-5.5 GPa. When the set pressure was reached, the pressure holding stage was entered and heating began. The initial heating was carried out at a rate of 10-20 ℃ / min until it reached 1500 ℃ and was maintained at this temperature for 10 minutes to ensure the stability of the cavity and release internal stress. Next, heating was continued at a rate of 5 ℃ / min to a range of 1800 to 2200 ℃ and maintained at this temperature for 10 to 30 minutes. During this process, the Fe column melted, and the boron (B) and nitrogen (N) atoms in the h-BN dissolved in the melt and formed nuclei at the contact surface between the edge of the Fe melt and the h-BN tube, as shown in Figure 2. Figure 2 (b) As shown in the left figure. The crystal growth is then controlled by cooling at a rate of 1-5 ℃ / min. Too fast cooling may affect the size and quality of the crystal, while too slow cooling has limited contribution to size growth. Figure 2 (b) The right figure shows a schematic diagram of the crystal after growth.

[0043] Figure 3 The researchers demonstrated that h-BN single crystals were encapsulated in Fe, Ni, and Cr columns using iron (Fe), nickel (Ni), and chromium (Cr) as solutes under high temperature and high pressure conditions. The metal Fe (Ni or Cr) was then removed by dilute hydrochloric acid (HCl), and finally washed with pure water and anhydrous ethanol and dried in an oven at 70 °C to obtain a pure h-BN single crystal sample.

[0044] Figure 4 The effect of adjusting the growth temperature, pressure and holding time on the size and yield of h-BN single crystals is demonstrated. At 5 GPa, the holding temperatures are set to 1800, 1950, 2100 and 2200 °C, and the holding time is 30 minutes. The h-BN single crystals grown are as follows: Figure 4 When the holding temperature is 1800 °C, the size of the single crystal is very small, only 1-2 mm, and mainly presents tower, pyramid or cone shapes (see Figure 5 (a) Optical micrograph), the color is gray, which may be due to the presence of a large amount of melt that has not been eliminated. When the temperature rises to 1950 °C, the color of the h-BN single crystal obviously changes from gray to white, and the morphology gradually changes to flake (see Figure 5(b)), which shows that as the temperature increases, the growth of h-BN single crystals along the c-axis direction (perpendicular to the h-BN layer direction) is weakened, while the growth along the a, b-axis direction (parallel to the h-BN layer direction) is strengthened. When the temperature reaches 2100 ℃, the single crystal basically presents a lamellar morphology, and the size rapidly increases to about 5-10 mm. At 2200 ℃, the crystal size reaches about 10 mm, and the yield is significantly improved, indicating that as the temperature approaches 2200 ℃, the solubility of B and N atoms in the Fe melt (or Cr, Ni, Fe / Cr, Fe / Ni and Cr / Ni melt) further increases, which is conducive to the rapid growth of the crystal and the acquisition of large-sized crystals.

[0045] At a fixed temperature of 2200 °C, the growth pressure was set to 2, 3, 4, and 5 GPa. The results showed that the growth yield of h-BN single crystals was similar at 2-4 GPa, but decreased at 5 GPa (see Figure 4 (b)), which indicates that the solubility of B / N atoms in high-temperature Fe melt may have a peak. In addition, excessive pressure may promote the transformation of h-BN to cubic boron nitride (c-BN), which may be the reason for the decrease in yield. It should be noted that for the case of more melt, appropriately increasing the pressure helps to reduce the fluidity of the Fe melt to maintain the stability of the experiment. The inventors also explored the effect of the holding time on the crystal yield, such as Figure 4 As shown in (c), increasing the holding time significantly improves the yield of h-BN single crystals. Figure 4 (d) and (e) respectively show the yield and size of h-BN single crystals obtained at 4 GPa pressure and 2200 °C for 1 hour. Hundreds of 1 cm and thousands of 1-3 mm h-BN single crystals can be obtained in a single growth.

[0046] X-ray diffraction (XRD) characterization of monolayer hexagonal h-BN (e.g. Figure 6 (a) shows that in the range of 10 to 90 degrees, only the diffraction peaks of 002, 004 and 006 are observed, and no diffraction peaks of other crystal planes are detected, which indicates the high crystallinity of the crystal. The half-peak width of the 006 diffraction peak is analyzed, and its width is 0.13°, which is comparable to 0.14° of high-quality h-BN single crystals reported in the current literature, reflecting that the h-BN single crystals prepared by the inventors have internationally advanced quality. Figure 6 (b) shows the Raman spectrum of h-BN single crystal. The peaks at 52.5 cm⁻¹ and 1365.7 cm⁻¹ correspond to the interlayer shear low-frequency vibration mode of h-BN (A g ) and the in-plane reverse high-frequency vibration mode of BN atoms (E 2g), as shown in the inset. The presence of low-frequency vibration modes reflects the degree of crystallinity of h-BN. This mode usually only appears in single crystal h-BN in the material, indicating that the h-BN single crystal prepared by the inventors has a significant thickness (~500 microns). According to E 2g The half-peak width of the vibration mode can be used to evaluate the crystallinity of h-BN. The half-peak width of the single-crystal boron nitride prepared by the inventors is about 7.9 cm⁻¹ (e.g. Figure 6 (c)), which is comparable to the high-quality h-BN single crystals reported in the world (>7.8 cm⁻¹). In addition, the inventors found that E 2g The half-peak width and peak position show an approximately linear decreasing relationship ( Figure 6 (d)), which may be related to the phonon softening caused by the introduction of internal defects. This relationship can also be used to evaluate the quality of the material. In order to evaluate the content of internal impurities such as oxygen and carbon, the inventors analyzed the samples by UV-visible absorption spectroscopy (such as Figure 6 (e)). Generally, the introduction of oxygen and carbon atoms will form specific pseudo-levels in h-BN, reducing the intrinsic band gap. In the inventors' data, no obvious absorption was observed in the entire 2 to 6 eV range, indicating that the sample has a high purity. Figure 6 As shown in (f), a thickness of 21 nm was prepared by mechanical exfoliation, and the critical breakdown field strength was calculated, which is 50% higher than the typical BN value of 800 MV / m, indicating that it has excellent dielectric properties and reflects the extremely low impurity content inside the h-BN single crystal.

[0047] The above is a further detailed description of the present invention, which should not be regarded as a limitation on the specific implementation of the present invention. For ordinary technicians in the technical field to which the present invention belongs, simple deduction or replacement without departing from the concept of the present invention is within the protection scope of the present invention.

Claims

1. A method for preparing industrial-grade large-size hexagonal boron nitride single crystals, characterized in that: The following steps are involved: 1) Place the metal core column in the boron nitride tube and pressurize it to a growth pressure of 2 to 6 GPa. After reaching the set pressure, enter the pressure holding stage; 2) Heating to 1000-1500°C at a rate of 10-20°C / min and keeping warm to release internal stress; 3) Continue heating at a rate of 10-20 °C / min to reach a growth temperature of 1800-3000 °C, and maintain at this temperature for 0.5-2 hours; 4) The crystal growth is controlled by cooling at a rate of 1 to 5 °C / min. After the crystal growth is completed, the metal is removed, and the crystal is washed and dried to obtain a hexagonal boron nitride single crystal.

2. The preparation method according to claim 1, characterized in that: The diameter ratio of the metal core column and the boron nitride tube is 0.65-0.

7.

3. The preparation method according to claim 1, characterized in that: The height ratio of the metal core column to the boron nitride tube is 0.65 to 0.

67.

4. The preparation method according to claim 1, characterized in that: The diameter difference between the boron nitride tube and the metal core column is not less than 2 mm.

5. The preparation method according to claim 1, characterized in that: The metal core column is made of Fe, Ni, Cr or Fe / Ni, Fe / Cr, Cr / Ni alloy.

6. The preparation method according to claim 1, characterized in that: The growth pressure is 2 to 5.5 GPa.

7. The preparation method according to claim 1, characterized in that: The growth temperature is 2000-2200°C.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The single crystal is grown at a pressure of 4 GPa and maintained at 2200° C. for 1 hour.

9. The preparation method according to any one of claims 1 to 7, characterized in that: The purity of the boron nitride tube is not less than 99.999%.

10. The preparation method according to any one of claims 1 to 7, characterized in that: Metal removal by pickling.

Citation Information

Patent Citations

  • Manufacturing method for cubic boron nitride crystal

    CN104607110A

  • Preparation method of large-sized hexagonal boron nitride monocrystals

    CN109695053A

  • Hexagonal boron nitride single crystal growth method

    CN113818072A

  • Preparation of cubic boron nitride

    JP1983204809A

  • Systems and methods for growth of silicon carbide over a layer comprising graphene and / or hexagonal boron nitride and related articles

    WO2019246515A1